Climate Variability on Phenology of Asiatic Mangrove Forest (Rhizophora mucronata Lam.) in Yaring Mangrove - เจ๊ะหลง, อิสมะแอ; ทองไชย, อลภา; ปาลนกวิน, อาเด่น (KKU Science Journal, 2016)
The effect of climate variability on phenology of leaf flushing, flowering and fruiting of asiatic mangrove was conducted in Yaring mangrove forest in Yaring district, Pattani province during 2011-2012. In 2011, the average of rainfall, evaporation, air temperature and soil moisture were 2259.30 ml./year, 614.29 ml./year, 33.57 oC/month and 33.45%/month, respectively. The results showed that the trees of asiatic mangrove flushed, flowered and fruited in May–July, September–October and November-December. In 2012, the average of rainfall (2407.50 ml./year), evaporation (598.36 ml./year), average air temperature (33.96 oC/month) and soil moisture (30.26%/month). The flushing and flowering of asiatic mangrove occurred in August– September and November–December. Thus, climate variability might be the main factor on leaf flushing, flowering and fruiting of asiatic mangrove.